Envolvimento das cininas na dor do tipo fibromialgia induzida por reserpina e o efeito dos inibidores da enzima conversora de angiotensina I em camundongos - Brusco, Indiara (2019)
Fibromyalgia is a chronic disease potentially disabling, characterized by widespread pain and a range of comorbidities as hypertension, besides not having specific pathophysiology or appropriate treatment. Evidence has demonstrated the contribution of kinins and their B1 and B2 receptors in chronic painful conditions. Additionally, the use of angiotensin I converting enzyme (ACE) inhibitor drugs by hypertensive patients has been associated with a potentiation of painful symptoms. Thus, we investigated the involvement of kinin B1 and B2 receptors in the reserpine-induced fibromyalgia-like pain and the effect of ACE inhibitors on this pain. For the induction of fibromyalgia model, male Swiss mice received one subcutaneous injection of reserpine (1 mg/kg, s.c.) once daily for 3 consecutive days. Nociceptive parameters such as mechanical and cold allodynia and spontaneous nociception, besides burrowing, thigmotaxis, forced swimming, and muscle strength test were evaluated at one day after the last reserpine administration. The role of kinin B1 and B2 receptors was investigated using knockout mice or pharmacological antagonism. Additionally, kinin B1 and B2 receptors expression and the bradykinin and monoamines levels were analyzed in the sciatic nerve, spinal cord and cerebral cortex of the animals. The effect of ACE inhibitors was evaluated on nociceptive parameters (mechanical and cold allodynia and spontaneous nociception) in animals previously treated with reserpine and also treated with kinin receptor antagonists. The bradykinin levels, as well as the activity of ACE and kininase I also were measured. Knockout mice for the B1 and B2 kinin receptor prevented the reserpine-induced mechanical allodynia. The antagonism of kinin B1 and B2 receptors also reduced the mechanical allodynia, the cold allodynia, and the spontaneous nociception reserpine-induced. The reserpine altered thigmotaxis, burrowing, forced swimming, and grip strength behavior of the mice. Moreover, reserpine increased the kinin B1 and B2 receptors expression and the kinin levels, as well as, reduced the monoamines levels in peripheral and central structures. The ACE inhibitors enalapril and captopril increased the reserpine-induced mechanical allodynia and this increase was prevented by kinin B1 and B2 receptor antagonists. Submaximal doses of substance P and bradykinin caused spontaneous nociception and increased mechanical allodynia in animals treated with reserpine. The reserpine administration associated with ACE inhibitors increased and bradykinin levels and inhibited the ACE activity in structures involved in the pain modulation. We evidence that kinins and their B1 and B2 receptors are involved in the fibromyalgia-like pain. In addition, we can suggest that therapy with ACE inhibitors in hypertensive patients and with fibromyalgia requires a careful analysis since this could potentiate their painful symptoms. Thus, hypertension treatment in patients with fibromyalgia could include classes of antihypertensive drugs diferents from ACE inhibitors. Our results indicate that kinin receptor antagonists may be promising drugs for relieving the pain of patients with fibromyalgia including those in treatment with ACE inhibitors.